Generating Paclitaxel-Resistant in Cervical Cancer HeLa Cell Line - Bashari, Muhammad Hasan; Damara, Fachreza Aryo; Hardani, Isna Nisrina; Pradini, Gita Widya; Putri, Tenny; Ariyanto, Eko Fuji (Indonesian Society for Cancer Chemoprevention, 2020)
Cervical cancer is one of the most leading causes of women death. Currently, paclitaxel is still one of the main therapeutic regimens for cervical cancer patients. However, some patients developed to be paclitaxel-resistant. Hence, studies to find out the novel strategies to resolve this problem are important. Generating resistant cancer cell lines can be utilized as the potent tool to evaluate the efficacy of any therapeutic agent toward cancer drug-resistant problems. Current studies describing the methods to establish chemoresistance are lacking. Moreover, study in Indonesia conducting chemoresistance in cell line is limited. This study was aimed to elaborate the characteristics of HeLa cells during generation of paclitaxel-resistant cervical cancer cells. The parental HeLa cells were exposed to an escalating concentration of paclitaxel for a long time period. Subsequently, cells were divided into two groups for the evaluation of resistance characteristics. The values of inhibitory concentration 50 (IC50) and inhibitory concentration 90 (IC90) were analyzed using 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide (MTT) assay. Our data showed that the longer exposing periods of paclitaxel, the higher IC50 and IC90 values of HeLa cells are. IC90 of paclitaxel in HeLa Pac RB was increased from 69 pM, 440 pM, 2,561 pM and 10,337 pM on 0th, 1st, 2nd, 3rd and 4th months, respectively. Interestingly, the resistant cells were recovered to be paclitaxel-sensitive when they were not being continuously exposed to paclitaxel. In addition, the paclitaxel resistant cells become less sensitive against 5-FU but not doxorubicin, cisplatin and etoposide. We were able to generate cervical cancer HeLa paclitaxel-resistant cell line. These cell line could potentially be utilized for further studies in order to understand the molecular mechanisms of drug resistance in cervical cancer and as a tool for cancer drug discovery.Keywords: cervical cancer, drug resistant cell line, paclitaxel resistant cells, stepwise escalating concentration.